Intellectual skills and strategic learning in students of general studies of a private university of Lima - Peña Miranda, Carlos Alberto (2019)
The objective of this research was to establish the correlations between the Intellectual Skills and the Strategic Learning in a sample of students of General Studies from a Private University of Lima. The research design used is the non-experimental of a correlational type. A sample of 348 subjects was used, to whom the Inventory of Intellectual Skills of Rosario Lajo and the Inventory of Strategic Learning of Manuel Torres were applied. The statistical results obtained show the existence of signiﬁcant and positive correlations between both variables (r = 0,77), which allowed the acceptance of the ﬁrst research hypothesis. Moreover, the results show the existence of positive and signiﬁcant relations of all the dimensions of the va-riables, intellectual skills and strategic learning; therefore, all the studied hypotheses were accepted.